Classification of stillbirth by the International Classification of Diseases for Perinatal Mortality using a sequential approach: A 20‐year retrospective study from Thailand. Issue 5 (17th February 2022) - Taweevisit, Mana; Nimitpanya, Panachai; Thorner, Paul S.
Abstract: Aim: The International Classification of Diseases for Perinatal Mortality (ICD‐PM) is a system for recording causes of perinatal death. In this system, placental pathology is considered a "maternal condition" and this category does not cover the spectrum of placental pathology that can impact on perinatal death. The aim of the study was to apply a wider spectrum of placental pathology as a separate parameter for classifying death in the ICD‐PM. Methods: All autopsy reports at a single institution over a 20‐year period (2001–2020) were reviewed. Causes of stillbirth were analyzed in a sequential manner: step 1, clinical history and laboratory results; step 2, placenta; and step 3, autopsy; and classified at each step according to the ICD‐PM. Results: The review identified 330 cases, including 126 antepartum and 204 intrapartum deaths. Step 1 identified a cause in 176 (86%) intrapartum deaths and 64 (51%) antepartum deaths. The addition of placental pathology (step 2) changed the cause of death in 12% of cases, with causes now identified in 190 (93%) intrapartum and 89 (71%) antepartum deaths. Adding step 3 did not identify any additional causes of death. Conclusion: The accuracy of the ICD‐PM classification is dependent on the data available. Placental pathology made a significant difference in assigning causes of death in our series, stressing the importance of placental examination. Determination of the cause of death based on clinical history and laboratory data alone may be inaccurate, and less useful for comparative studies and planning prenatal care.